2015
DOI: 10.1021/nl5046473
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Assembled Nanoparticle Rings Exhibit Electric and Magnetic Resonances at Visible Frequencies

Abstract: Metallic nanostructures can be used to manipulate light on the subwavelength scale to create tailored optical material properties. Next to electric responses, artificial optical magnetism is of particular interest but difficult to achieve at visible wavelengths. DNA-self-assembly has proved to serve as a viable method to template plasmonic materials with nanometer precision and to produce large quantities of metallic objects with high yields. We present here the fabrication of self-assembled ring-shaped plasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
146
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(149 citation statements)
references
References 40 publications
0
146
0
Order By: Relevance
“…[64] The topography of the patterned substrate provided a sufficient bias to control the long-range order of the block copolymer. [70][71][72][73] When the DNA assembly is precisely controlled by using a patterned surface, DNA origami can be a powerful tool, for example, by dictating the arrangement of sub 10 nm components (gold nanoparticles) over large scale areas ( Figure 2C). [63][64][65][66] Template-directed assembly of molecules, DNA, and nanoparticles can also give rise to micro and nanoscale structures with promising optical responses.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…[64] The topography of the patterned substrate provided a sufficient bias to control the long-range order of the block copolymer. [70][71][72][73] When the DNA assembly is precisely controlled by using a patterned surface, DNA origami can be a powerful tool, for example, by dictating the arrangement of sub 10 nm components (gold nanoparticles) over large scale areas ( Figure 2C). [63][64][65][66] Template-directed assembly of molecules, DNA, and nanoparticles can also give rise to micro and nanoscale structures with promising optical responses.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…Roller et al recently reported on spectral changes occurring in 2D particle clusters supported by a DNA framework due to drying, with the main dipole resonance shift being the result of shrinkage of the cluster during drying. 6 Using AuNPs mono-conjugated to three-dimensional DNA “rung” structures, both discrete and extended linear assemblies were controllably prepared via addition of various templating backbone strands. 7 While exquisite structural control was demonstrated, the relationship between deformation and spectral properties was not pursued.…”
Section: Introductionmentioning
confidence: 99%
“…Also direct metallization of origami to form nanoscale wires and other metallic shapes has been investigated widely [20], but this approach does not provide an easy way to produce functional electronic devices. Many groups have demonstrated optical devices based on organizing metallic NPs exhibiting localized surface plasmon resonance [21][22][23][24], but despite the promises only few DNA based electrical devices or studies have been realized [19,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%